2002
DOI: 10.1159/000066792
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamics during Development of Hypertension in Young Spontaneously Hypertensive Rats

Abstract: Background/Aims: Cross-transplantation studies between animals with genetic hypertension and normotensive animals indicate a key role of the kidney in development of hypertension, and studies in young spontaneously hypertensive rats (SHR) have shown reduced glomerular filtration rate (GFR) and renal blood flow (RBF) for a short period at the age of 4–6 weeks during blood pressure increase. We tested the hypothesis that a decline in GFR during development of hypertension in SHR might be more pronounced in juxta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Some studies did not observe an increased blood pressure until 6 wk of age; others (22) found high blood pressure even in the newborn SHR. The gradual increase in blood pressure from 6 wk of age seen in the present study is supported by several studies (11,33).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies did not observe an increased blood pressure until 6 wk of age; others (22) found high blood pressure even in the newborn SHR. The gradual increase in blood pressure from 6 wk of age seen in the present study is supported by several studies (11,33).…”
Section: Discussionsupporting
confidence: 91%
“…Methylphenidate increased endogenous dopamine activation of DRD2 in WKY but did not alter DRD2 function in SHR striatum Sagvolden (2000) Reanalysis of data ADHD-like overactivity, motor impulsiveness, and deficient sustained attention in SHR compared to several rat strains Bull et al (2000) Differential reinforcement of low rate responding in an operant task WKY performed better than SHR and Sprague-Dawley rats when low rates of responding were required but performed poorly compared with the other rat strains in those parts of training that required high response rates Russell (2001) In vitro superfusion Increased glutamate-stimulated release of [ 3 H]norepinephrine from SHR prefrontal cortex slices is antagonized by AMPA antagonist, CNQX Lehohla et al (2001) NMDA-stimulated uptake of 45 Ca 2+ Decreased In vitro 45 Ca 2+ uptake into barrel cortex slices of SHR Fellner and Arendshorst (2002) Cytosolic Ca 2+ measured with fura-2 fluorescence Store-operated calcium entry into vascular smooth muscle cells was greater in SHR than WKY. L-channel calcium entry was greater in SHR Christiansen et al (2002) Blood pressure measurement SHR and WKY have similar body weight. Mean arterial blood pressure was not different at 2 weeks but increased from 4 to 10 weeks of age Ueno et al (2002b) Open-field exploration Methylphenidate (0.01-1 mg/kg, i.p.)…”
Section: Referencementioning
confidence: 89%
“…One of the proposed mechanisms of the initiation of hypertension in SHR involves a primary defect in renal sodium (Na + ) excretion2-8. Over time, this defect necessitates an increase in renal perfusion pressure, an adaptation which becomes central to the development and maintenance of hypertension9, 10.…”
Section: Introductionmentioning
confidence: 99%